The Factors Affecting the Audit Quality with the Understanding on Information Systems as the Moderating Variable - Oktavianto, Dimas Dwi; Suryandari, Dhini (Accounting Analysis Journal, 2018)
This study aims to examine the role of understanding of information systems in moderating the influence of auditor experience and audit complexity on audit quality. The population in this study is the auditor at the Public Accounting Firm in Semarang City as many as 17 KAP with a population of 255 auditors. The sampling technique uses convenience sampling. The number of samples that can be processed by 54 respondents. The test was done by multiple regression test to test the independent variable and the interaction test (moderated regression analysis) to test the moderation variable. The results showed that partially experience of auditors does not affect the quality of audit, audit complexity negatively affect the quality of audits, and understanding of information systems have a positive effect on audit quality. The result of moderation testing shows that the understanding of the information system is not able to moderate the influence of the auditor’s experience on audit quality but can moderate the effect of audit complexity on audit quality. The conclusion of this study is that high audit complexity will reduce audit quality, and understanding of good information system will improve audit quality, and understanding of good information system will weaken audit complexity to audit quality.